2011
DOI: 10.1002/ange.201007417
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Anionic and Lewis Acid Stabilized N‐Heterocyclic Oxoboranes: Their Facile Synthesis from a Borinic Acid

Abstract: BO im Doppelpack: Metallfreie anionische Oxoborane und Lewis‐Säure‐stabilisierte Oxoborane mit formaler B‐O‐Doppelbindung lassen sich leicht aus einer N‐heterocyclischen Borinsäure in Gegenwart von N‐heterocyclischen Carbenen (NHCs) bzw. Lewis‐Säuren erhalten (siehe Schema).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 48 publications
0
10
0
1
Order By: Relevance
“…92.6% located at oxygen), which can be also certified by the high positive charge (1.14+) of B2 atom from natural population analysis. The Wiberg bond index value of 1.207 for the B2O3 bond is larger than those of the neutral oxoboranes III (1.07) and IVa (1.123) 6,7 but smaller than that of the acid free anionic oxoborane X (1.40), 11b supporting its partial double-bond property. For comparison, the anionic oxoborane fragment DmpBO − (OH)3′ was also theoretically calculated, and the obtained BO double-bond distance is only 0.023 Å shorter than that calculated for 3 (1.305 vs 1.282 Å).…”
Section: ■ Results and Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…92.6% located at oxygen), which can be also certified by the high positive charge (1.14+) of B2 atom from natural population analysis. The Wiberg bond index value of 1.207 for the B2O3 bond is larger than those of the neutral oxoboranes III (1.07) and IVa (1.123) 6,7 but smaller than that of the acid free anionic oxoborane X (1.40), 11b supporting its partial double-bond property. For comparison, the anionic oxoborane fragment DmpBO − (OH)3′ was also theoretically calculated, and the obtained BO double-bond distance is only 0.023 Å shorter than that calculated for 3 (1.305 vs 1.282 Å).…”
Section: ■ Results and Discussionmentioning
confidence: 87%
“…5 Similarly, the Cui and Kinjo groups reported the formation of oxoboranes II and III from Lewis acid-induced intramolecular proton migration of borinic acid precursors, respectively. 6 Rivard and co-workers demonstrated that oxoboranes IVa,b featuring ClBO and HOBO fragments can be stabilized by using a combination of N-heterocyclic carbene (NHC) and borane. 7 Different from their neutral counterparts, an anionic BO − unit is isoelectronic with carbon monoxide and is predicted to be an extremely strong σ donor.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In the 31 P{ 1 H} NMR spectrum, the inequivalent P i Pr 2 groups display at 4.2 and 1.9 ppm doublets with a P−P coupling constant of 25.6 Hz. (11), Os−P2 = 2.3677 (11); C1−Os−C3 = 175.12 (19), P1−Os−P2 = 114.10(4), P2−Os−C2 = 123.63 (17), P1−Os−C2 = 122.09 (17). This study shows a novel reaction in the chemistry of hydroxotransition-metal complexes, reveals the existence of boroxide derivatives of platinum group metals, demonstrates that the reductive elimination of borinic acids from hydride metalboroxide compounds is disfavored with regard to the release of molecular hydrogen and to the reductive elimination of water from hydride-metal-hydroxo counterparts, and enlarges the range of metal ions stabilizing compounds with κ 2 -P,Pcoordinated ether-diphosphines.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…17 This is consistent with that observed by Braunschweig and co-workers for the M−chalcogene−B angle, in the borachalcogene complexes Cp(CO) 2 Mn[EB t Bu-(IMe)] (E = S, Se, Te), which increases by going up in the group, i.e., in the sequence Te < Se < S. 18 However, in contrast to the Braunschweig's compounds, the O1−B bond length of 1.332( 6) Å reveals a short chalcogene−boron single bond. 19 The DFT optimized structure (Figure 1b) confirms the trihydride character of the OsH 3 unit, although the calculated separations between H01 and H02 and between H02 and H03 of 1.57 and 1.64 Å, respectively, suggest the presence of weak nonclassical interactions between the hydride ligands. 20 The 1 H NMR spectra of 2 and 3 in toluene-d 8 also support the presence of weak nonclassical interactions between the hydride ligands.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Metallfreie anionische Oxoborane (19) und Lewis‐Säure‐stabilisierte Oxoborane (20) mit formaler B‐O‐Doppelbindung lassen sich leicht aus einer N‐heterocyclischen Borinsäure (18) in Gegenwart von N‐heterocyclischen Carbenen (NHCs) oder Lewis‐Säuren erhalten. Die Oxoborane sind formal isoelektronisch mit Harnstoffderivaten 1_33…”
Section: Fortschritte In Der Chemie Der Elemente Der 13 Gruppeunclassified